Acceptability of chronic liver disease screening in a UK primary care setting: a qualitative evaluation. Issue 11 (18th November 2020) - Knight, Holly; Harman, David; Morling, Joanne R; Aithal, Guruprasad; Card, Timothy; Guha, Indra Neil; Bains, Manpreet
Abstract : Objectives: The increasing incidence of chronic liver disease (CLD) in the UK may be attributed to a rise in preventable risk factors, including hazardous alcohol use and type 2 diabetes. Transient elastography (TE) can rapidly stratify risk of CLD in primary care populations and provide an opportunity to raise patient awareness of risk factors. This study explores patients' experiences of TE screening in a primary care setting. In addition, patient awareness of CLD risk is explored. Study design and setting: This study used a qualitative process evaluation of a community screening pathway for CLD (Nottingham, UK). Participants completed semistructured interviews, which were audio-recorded, transcribed verbatim and analysed thematically. Participants: Twenty adults were purposively recruited 6 months to 2 years after TE screening. Inclusion criteria included (1) hazardous alcohol use, (2) type 2 diabetes and/or (3) persistently elevated liver enzymes without known cause. Results: Undergoing TE in primary care was seen as acceptable to most participants. Hazardous alcohol use was identified as the primary cause of CLD; no participants were aware of metabolic risk factors. TE improved understanding of personal risk factors and prompted contemplation of lifestyle changes across all TE stratifications. However, participants' perceptions of risk were altered by the healthcare providers' communication of TE scores. Conclusions: High acceptability of TE, regardless of the risk factor, provides strong support for inclusion of TE stratification in primary care. Findings highlight the positive impact of receiving TE on risk awareness. Future clinical iterations should improve the structure and communication of TE results to patients.